MAPbBr3−xIx Crystals Improved by Accurate Solution-Grown Procedure for Alpha Particle Detection - Liu, Xin; Fu, Jinghua; Zhao, Dou; Hao, Yingying; Zhu, Hao; Xu, Meng; Zhang, Binbin; Jie, Wanqi; Xu, Yadong (Frontiers in Physics, 2020)
High-quality organic–inorganic halide perovskite brings an opportunity for ideal nuclear radiation detection due to its large carrier mobility, lifetime, and heavy atoms. However, the relatively low bulk resistivity restricts its development for alpha particles and X/γ-ray detectors. Here, we report on the MAPbBr3−xIx (MPB:I) perovskite crystals grown using the modified inverse temperature crystallization method. Based on the measured supersolubility and solubility curves, the heating procedure was accurately designed to control the nucleation and growth rate. The resulting MPB:I single crystals exhibit higher bulk resistivity of 1.4 × 109 Ω cm, which is 10 times that obtained from the traditional inverse temperature crystallization method. Finally, an uncollimated 0.8 μCi 241Am @5.48 MeV alpha particles source was adopted to evaluate the MPB:I single crystals at room temperature condition. The electron mobility (μe) and mobility-lifetime product (μτ)e of (264.6 ± 6.5) cm2 V−1 s−1 and (2.6 ± 0.3) × 10−3 cm2/V, respectively, were obtained.